Government Policies in Economic Empowerment of Muslim Communities in the Digital Economy Era - Fajar Sukma; Zulheldi Zulheldi (El-Mashlahah, 2021)
ABSTRACTThis article highlighted the role and policies of the government and its staff in carrying out the tasks or functions of community empowerment, including identifying the supporting and hindering factors in the community empowerment process. Community empowerment also has several principles in its implementation, namely awareness of the community, providing education and training, organizing, developing strengths, and developing dynamics (decisions in the hands of the community itself). Community empowerment is focused on various aspects related to people's lives as a nation's society, namely empowerment in the fields of education, economy, socio-culture, psychology, and politics in the era of the digital economy. Through literature studies and qualitative approaches aimed to examine and interpret the events related to policies and the role of government, then compare to Islamic governments in the past. In the era of Amirul Mukminin bin Al-Khattab as the second caliph, he ran the government firmly but was very sensitive to his people. The policies, that he issued, were for the benefit of the people, not only Muslims but also all citizens who live in the authority of Umar's caliphate. These policies in community empowerment during Umar's time should be interpreted in the current context. The era is known as the digital age, of course, it needs to modify the policies of the previous era so that they can be relevant and able to be implemented in real terms.Keywords: Government Policy, Community Empowerment, Digital Economy Era.ABSTRAKArtikel ini menyoroti peran dan kebijakan pemerintah dan jajarannya dalam menjalankan tugas atau fungsi pemberdayaan masyarakat, termasuk mengidentifikasi faktor pendukung dan penghambat proses pemberdayaan masyarakat. Pemberdayaan masyarakat juga memiliki beberapa prinsip dalam pelaksanaannya, yaitu penyadaran terhadap masyarakat, memberikan pendidikan dan pelatihan, pengorganisasian, pengembangan kekuatan, dan pengembangan dinamika (keputusan di tangan masyarakat itu sendiri). Pemberdayaan masyarakat difokuskan pada berbagai aspek yang berkaitan dengan kehidupan masyarakat sebagai masyarakat bangsa, yaitu pemberdayaan di bidang pendidikan, ekonomi, sosial budaya, psikologi, dan politik di era ekonomi digital. Dengan melakukan studi pustaka dan pendekatan kualitatif untuk menelaah dan menginterpretasikaan kejadian-kejadian yang terkait dengan kebijakan serta peran pemerintah dan membandingkannnya dengan pemerintahan Islam di masa lalu. Di era Amirul Mukminin bin Al-Khattab sebagai khalifah ke dua, ia menjalankan pemerintahan dengan tegas namun sangat peka terhadap rakyatnya. Kebijakan-kebijakan yang dikeluarkannya adalah untuk kemaslahatan umat, tidak hanya umat muslim tetapi juga seluruh warga yang berada dalam naungan kekhalifahan Umar. Kebijakan-kebijakan dalam pemberdayaan masyarakat di masa Umar tersebut patut diintepretasikan pada konteks sekarang. Zaman yang dikenal dengan zaman digital tentu perlu modifikasi kebijakan era dulu, sehingga dapat relevan dan mampu diterapkan secara nyata.Kata Kunci: Kebijakan Pemerintah, Pemberdayaan Masyarakat, Era Ekonomi Digital.